2021
DOI: 10.3390/jcm10092019
|View full text |Cite
|
Sign up to set email alerts
|

Poorly Differentiated Neuroendocrine Larynx Carcinoma: Clinical Features and miRNAs Signature—A New Goal for Early Diagnosis and Therapy?

Abstract: Laryngeal neuroendocrine carcinomas (LNECs) are rare and highly heterogeneous malignancies presenting a wide range of pathological and clinical manifestations. Herein, we retrospectively characterize ten patients diagnosticated with LNEC, five of which were defined as well-moderately differentiated neuroendocrine carcinomas, and five that were defined as poorly differentiated neuroendocrine carcinomas, according to the latest WHO classification. Clinical features were analyzed and compared between the two subg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Our patient showed moderate-to-severe cellular atypia and positivity for the neuroendocrine marker synaptophysin and epithelial marker CK7, which was consistent with the diagnosis of high-grade NEC [6] . Surgery combined with chemoradiotherapy is the main treatment strategy for NEC in the head and neck, and the prognosis is associated with the pathological type and differentiation of the tumor [17] . Esmati et al reported a patient with limited tongue NEC who underwent partial excision followed by chemoradiotherapy, without signs of recurrence at the approximately 5-year follow-up [5] .…”
Section: Discussionmentioning
confidence: 99%
“…Our patient showed moderate-to-severe cellular atypia and positivity for the neuroendocrine marker synaptophysin and epithelial marker CK7, which was consistent with the diagnosis of high-grade NEC [6] . Surgery combined with chemoradiotherapy is the main treatment strategy for NEC in the head and neck, and the prognosis is associated with the pathological type and differentiation of the tumor [17] . Esmati et al reported a patient with limited tongue NEC who underwent partial excision followed by chemoradiotherapy, without signs of recurrence at the approximately 5-year follow-up [5] .…”
Section: Discussionmentioning
confidence: 99%
“…In the future, different miRNA combinations may be able to detect different subtypes of PCOS. Additionally, studies demonstrated that miRNA expression had excellent prognostic scores only when discovered in early-stage of cancer [35,36]. The microRNA signatures may also help to identify these women in early stage and change treatment regimens in timely manner, when women respond poorly to progestin-based therapy leading to low currency of PCOS and hirsutism and acne [37].…”
Section: Discussionmentioning
confidence: 99%
“…Precision medicine has recently concentrated on the outstanding opportunities resulting from the potential to restore homeostatic miRNA levels to their therapeutic potential. This is tied to peculiar and specific patient profiles [69].…”
Section: Poorly Differentiated Neuroendocrine Larynx Carcinomamentioning
confidence: 99%